Impatience among preschool children and their mothers - Fabian Kosse; Friedhelm Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Using experimental data of children and their mothers, this paper explores the intergenerational relationship of impatience. The child's impatience stems from a delay of gratification experiment. Mother's impatience has been assessed by a choice task where the mothers faced trade-offs between a smaller-sooner and a larger-later monetary reward with a delay of six or twelve months. The findings demonstrate an intergenerational relationship in short-run decision making. Controlling for mother's and child's characteristics the child's impatience at preschool age is significantly correlated with the six month maternal reservation interest rate.
Keywords: C93; D03; D90; 330; time preferences; impatience; intergenerational transmission; field experiments; Zeitpräferenz; Kinder; Mütter; Persönlichkeitspsychologie; Test